2014
DOI: 10.1007/s11011-014-9625-1
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of alpha lipoic acid on high glucose-induced neurotoxicity in PC12 cells

Abstract: Hyperglycemia plays an important role in the development of diabetic neuropathy. In this study, we investigated the protective effects of alpha lipoic acid (ALA) against high glucose-induced neurotoxicity in PC12 cells as a suitable in vitro model for studying neuronal functions. PC12 cells were treated with high glucose (25 mg/ml for 24 h) in the absence and presence of ALA (100 μM for 24 h). The viability of PC12 cells was estimated by using MTT assay. The expression of pro- apoptotic Bax, anti- apoptotic Bc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 57 publications
1
29
0
Order By: Relevance
“…20 Fifty microgram protein was loaded onto a 12% SDS-PAGE and transferred on a nitrocellulose membrane.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…20 Fifty microgram protein was loaded onto a 12% SDS-PAGE and transferred on a nitrocellulose membrane.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…PC12 cell, a mature cell line from a rat pheochromocytoma, has been widely used in neurophysiological studies. In particular, these cells have served as a commonly used cellular model for studying the mechanisms underlying glucose neurotoxicity [ 21 23 ]. With regard to Lipin1, results from in vitro experiments which have shown that Lipin1 concentrations were reduced when PC12 cells were treated with HG and Lipin1 alleviated HG-induced neurotoxicity in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition AA administration significantly reduced MDA and SOD levels and significantly improved the activities of GPX and SOD in liver and brain tissues. The protective effect of ALA is derived from its ability to counteract ROS generation and exhibited beneficial role in the treatment of chronic liver diseases [24]. ALA treatment of HE -induced rats significantly decremented serum TNF-α and S100-β levels.…”
Section: Discussionmentioning
confidence: 99%